Effects of Vertical Integration Reform on Primary Healthcare Institutions in China: Evidence From a Longitudinal Study - Shasha Yuan; Fengmei Fan; Dawei Zhu (Kerman University of Medical Sciences, 2022)
Background  Integrated care is a global trend in international healthcare reform, particularly for piloting vertical integration involving hospitals and primary healthcare institutions (PHIs). However, evidence regarding the impact of vertical integration on primary healthcare has been mixed and limited. Our study aims to evaluate the empirical effects of vertical integration reform on PHIs in China, and examines variations across integration intensity (tight integration vs. loose collaboration). Methods  This study used a longitudinal design. The time-varying difference-in-difference (DID) method with a fixedeffect model for panel data was adopted. A total of 370 PHIs in the eastern, central, and western areas of China from 2009 to 2018 were covered. Outcome measures included the indicators at three dimensions regarding inpatient and outpatient service volume, patient flow between PHIs and hospitals and quality of chronic disease care (hypertension and diabetes). Results  Significant increases in absolute (the number) and relative (the ratio between PHIs and hospitals) volume of inpatient admissions have been found after reform under tight integration, peaking at 183% and 15.0% respectively, in the third reform year. The quality of hypertension and diabetes care (by indicators of control rate of blood pressure and blood glucose) showed significant improvements under both types of vertical integration after reform. It was much more distinct for the PHIs under tight integration, which had the most significant increase of 34.0% and 22.8% under tight integration for the control rate of hypertension and diabetes compared to the peak of 21.2% and 22.1% respectively under loose collaboration. Conclusion  Our findings suggest that vertical integration (especially tight integration) in China significantly contributed to strengthening primary healthcare in terms of inpatient services and quality of hypertension and diabetes care, providing empirical evidence to other countries on integrating primary healthcare-based health systems.